Christianity, empire, and the spirit : (re)configuring faith and the cultural - Medina, Néstor. (Theology and Mission in World Christianity, 2018)
In Christianity, Empire and The Spirit , Néstor Medina uncovers the cultural processes that play a crucial role in influencing how people understand reality, express the Christian faith, and think about God. He uses decolonial thinking, Latina/o theology, and Pentecostal theology to show how the cultural dimension is a central feature in the biblical text; was the force that coopted Christianity from the imperial era of Constantine onwards; and undergirded Western European colonialism and the missionary project. He engages with Protestant and Catholic articulations on "culture" and demonstrates how most theologians perpetuate Eurocentric frames for considering the relation between Christianity and the cultural dimension. Alternatively, he offers a theological proposal that recognizes the Spirit at work in the phenomena of cultures.